2017
DOI: 10.1039/c7ra05947g
|View full text |Cite
|
Sign up to set email alerts
|

Norsampsone E, an unprecedented decarbonyl polycyclic polyprenylated acylphloroglucinol with a homoadamantyl core from Hypericum sampsonii

Abstract: Norsampsone E (1), an unprecedented decarbonyl polycyclic polyprenylated acylphloroglucinol, together with one new and two known analogues (2-4), was isolated from the aerial parts of Hypericum sampsonii. Compound 1 featured an unusual homoadamantyl skeleton with the loss of C-4 carbonyl and followed by the formation of a new C-C bond between C-3 and C-5. Their structures and absolute configurations were elucidated by extensive NMR spectroscopy, single-crystal X-ray experiments, ECD calculations and CD compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The 1 H- and 13 C-NMR data of 2 showed the presence of a benzoyl group [δ H 7.33 (2H, br dd, J = 8.4, 7.4 Hz, H-13 and H-15), 7.45 (1H, br t, J = 7.4 Hz, H-14) and 7.56 (2H, br d, J = 8.4 Hz, H-12 and H-16); δ C 128.1 (C-13), 128.1 (C-15), 129.1 (C-12), 129.1 (C-16), 132.8 (C-14) and 134.5 (C-11)], a hydroxyl group [δ H 3.38 (1H, s, D 2 O exchangeable, OH-3)], a geranyl group [δ H 1.62, 1.68 and 1.69 (each 3H, each s, H-37, H-38 and H-32), 2.11 (2H, m, H-33), 2.14 (2H, m, H-34), 2.58 (2H, m, H-29), 5.10 (1H, br t, J = 6.7 Hz, H-35) and 5.40 (1H, br t, J = 7.5 Hz, H-30); δ C 16.2 (C-32), 17.7 (C-37), 25.8 (C-38), 26.3 (C-29), 26.4 (C-34), 40.2 (C-33), 118.5 (C-30), 124.1 (C-35), 131.7 (C-36) and 139.0 (C-31)], a prop-1-en-2-yl group [δ H 1.85 (3H, s, H-22), 5.01 (1H, br s, H-23) and 5.25 (1H, br s, H-23); δ C 21.7 (C-22), 118.5 (C-23) and 142.5 (C-21)] and two methyl groups [δ H 1.36, 1.44 (each 3H, each s, H-17 and H-18); δ C 21.7 (C-17) and 24.5 (C-18)]. Comparison of the 1 H- and 13 C-NMR data of 2 with those of norsampsone E [ 24 ] suggested that their structures were closely related, except that the benzoyl group at C-1 of 2 replaced the 1-isobutyryl group of norsampsone E [ 24 ]. This was supported by both HMBC correlations between H-12 (δ H 7.56) and C-10 (δ C 193.3), C-14 (δ C 132.8) and C-16 (δ C 129.1) and ROESY correlations between H-12 (δ H 7.56) and H-17 (δ H 1.36).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H- and 13 C-NMR data of 2 showed the presence of a benzoyl group [δ H 7.33 (2H, br dd, J = 8.4, 7.4 Hz, H-13 and H-15), 7.45 (1H, br t, J = 7.4 Hz, H-14) and 7.56 (2H, br d, J = 8.4 Hz, H-12 and H-16); δ C 128.1 (C-13), 128.1 (C-15), 129.1 (C-12), 129.1 (C-16), 132.8 (C-14) and 134.5 (C-11)], a hydroxyl group [δ H 3.38 (1H, s, D 2 O exchangeable, OH-3)], a geranyl group [δ H 1.62, 1.68 and 1.69 (each 3H, each s, H-37, H-38 and H-32), 2.11 (2H, m, H-33), 2.14 (2H, m, H-34), 2.58 (2H, m, H-29), 5.10 (1H, br t, J = 6.7 Hz, H-35) and 5.40 (1H, br t, J = 7.5 Hz, H-30); δ C 16.2 (C-32), 17.7 (C-37), 25.8 (C-38), 26.3 (C-29), 26.4 (C-34), 40.2 (C-33), 118.5 (C-30), 124.1 (C-35), 131.7 (C-36) and 139.0 (C-31)], a prop-1-en-2-yl group [δ H 1.85 (3H, s, H-22), 5.01 (1H, br s, H-23) and 5.25 (1H, br s, H-23); δ C 21.7 (C-22), 118.5 (C-23) and 142.5 (C-21)] and two methyl groups [δ H 1.36, 1.44 (each 3H, each s, H-17 and H-18); δ C 21.7 (C-17) and 24.5 (C-18)]. Comparison of the 1 H- and 13 C-NMR data of 2 with those of norsampsone E [ 24 ] suggested that their structures were closely related, except that the benzoyl group at C-1 of 2 replaced the 1-isobutyryl group of norsampsone E [ 24 ]. This was supported by both HMBC correlations between H-12 (δ H 7.56) and C-10 (δ C 193.3), C-14 (δ C 132.8) and C-16 (δ C 129.1) and ROESY correlations between H-12 (δ H 7.56) and H-17 (δ H 1.36).…”
Section: Resultsmentioning
confidence: 99%
“…Polycyclic polyprenylated acylphloroglucinols (PPAPs), characterized by highly oxygenated acylphloroglucinol-based cores adorned with the isoprenyl or geranyl side chains, are a special group of structurally fascinating natural products mainly isolated from the family Guttiferae. Adamantanes featuring a tricyclo[3.3.1.1]­decane skeleton and homoadamantanes with a tricyclo[4.3.1.1]­undecane skeleton are subclasses of PPAPs. These subclasses were derived from the enolic C-3 cyclizing onto C-27 and C-28 of normal endo -bicyclic polyprenylated acylphloroglucinols (BPAPs), respectively. , Additionally, these subclasses could also undergo cleavage or degradation of the acylphloroglucinol core and rearrangement to form diverse frameworks. The adamantane and homoadamantane-types PPAPs possessed extensive biological activities, including immunosuppressive, anti-inflammatory, antitumor, antiviral, and AChE inhibitory activities, highlighting the promising application prospects of these natural metabolites. ,, …”
Section: Introductionmentioning
confidence: 99%